2010
DOI: 10.1177/147323001003800436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Vitamin C on Oxygen Free Radical Production and Myocardial Enzyme after Tourniquet Ischaemia–Reperfusion Injury during Bilateral Total Knee Replacement

Abstract: This study investigated the effects of highdose vitamin C on oxygen free radical production and cardiac enzymes after tourniquet application and ischaemiareperfusion injury during bilateral total knee replacement (TKR) in elderly patients. In the vitamin C (VC) group (VC group, n = 16), during surgery, patients received a priming bolus of 0.06 g/kg vitamin C with 100 ml saline followed by 0.02 g/kg vitamin C mixed with 30 ml saline, intravenously. The control group (n = 16) received no intra-operative vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…In the last 10 years, it has been shown in several papers made in patients undergoing knee surgery with tourniquet ischemia, increases of lipid peroxidation markers in systemic blood (venous or arterial), measuring the concentration of TBARS (TBA reacting substance), MDA, F2-isoprostanes, or isofurans ischemia. [4][5][6][7][8][9][10][11][17][18][19] The main finding for our study was that reduced glutathione and polyunsaturated fatty acids were oxidized very quickly with an increase in a 100% of GSSG and MDA blood levels, but coinciding with a decrease in GSH levels at T 1 -T 3 in blood drained from operated knee (group K). These increases in GSSG and MDA blood levels were also observed in peripheral blood from a forearm vein (group V) at T 1 and T 2 , but at lower levels than in blood from the operated knee.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the last 10 years, it has been shown in several papers made in patients undergoing knee surgery with tourniquet ischemia, increases of lipid peroxidation markers in systemic blood (venous or arterial), measuring the concentration of TBARS (TBA reacting substance), MDA, F2-isoprostanes, or isofurans ischemia. [4][5][6][7][8][9][10][11][17][18][19] The main finding for our study was that reduced glutathione and polyunsaturated fatty acids were oxidized very quickly with an increase in a 100% of GSSG and MDA blood levels, but coinciding with a decrease in GSH levels at T 1 -T 3 in blood drained from operated knee (group K). These increases in GSSG and MDA blood levels were also observed in peripheral blood from a forearm vein (group V) at T 1 and T 2 , but at lower levels than in blood from the operated knee.…”
Section: Discussionmentioning
confidence: 87%
“…2,3 Lipids peroxidation is a chain reaction leading to oxidation of polyunsaturated fatty acids which break the structure of biological membranes and produce toxic metabolites such as malondialdehyde (MDA) and other stable degradation products of lipid peroxides, which play an important role in reperfusion damage because they act locally but also act in other distant organs as lungs and circulatory system. [4][5][6][7][8][9][10][11] Also recently have been reported two studies on tourniquet-induced I-R injury during lower extremity surgery, showing DNA damage in peripheral blood lymphocytes. 12,13 So far all studies on oxidative stress in patients undergoing knee surgery have used the systemic blood, usually from an arm vein or the radial artery.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies examined antioxidant interventions (Table ). One study examined both propofol and N‐acetyl‐cysteine, but propofol was used in a sub‐anaesthetic dose and we therefore categorised it in the antioxidant intervention group .…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the effect of vitamin C in patients undergoing bilateral knee replacement . The authors reported no postoperative clinical outcomes or complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation